Age-related features of some plasminogen activation system components content and activity in the blood of benign and malignant uterine body tumors - I. V. Kaplieva; G. V. Zhukova; V. R. Zakharchenko; E. M. Frantsiyants; E. V. Verenikina; Yu. A. Pogorelova; P. S. Kachesova; Yu. Yu. Kozel; N. A. Maximova; M. G. Ilchenko; E. I. Agarkova; A. S. Egorova (Исследования и практика в медицине)
Purpose of the study. Is to determine the features in the content and activity of some components of the plasminogen activation system in the blood of patients of different ages with leiomyomas (LM) and uterine corpus endometrial cancer (UCEC).Patients and methods. The study was carried out in patients with LM (n = 35) and UCEC T1a-2N0M0 (n = 56) of reproductive, perimenopausal and postmenopausal ages. Using ELISA methods, the content and activity of urokinase (u-PA), tissue plasminogen activator (t-PA), their inhibitor PAI-1, as well as the content of the soluble form of the u-PA receptor (su-PAR) were determined in the blood of patients. The Student´s test was used for statistical processing.Results. Regardless of the nature of the uterus tumor, it has been noted a significant increase in the activity and blood level of PAI-1 (up to 8 times, p < 0.01), especially pronounced in patients with UCEC of reproductive age. It was combined with the absence of changes or with a decreasing in blood level of su-PAR by more than 40 % (p < 0.05). We observed a rise of u-PA blood level without changes in one´s activity in patients with LM of perimenopausal age. And in patients with LM and UCEC of postmenopausal age an increase in u-PA blood level as well as elevation of u-PA activity (up to 3.9 times, p < 0.01–0.05) were noted. There was an increase in the calculated t-PA index (activity per unit mass) by 1.4–2.8 times (p < 0.05) in the most patients. The indicators of LM patients were characterized by the minimum value of the ratio “t-PA activity/u-PA activity in the blood” among all studied subgroups of patients. Age-related features of the researched parameters were observed more often in the cases of LM than in the cases of UCEC. The most pronounced differences between LM and UCEC were observed in patients of reproductive and postmenopausal age, characterized by stable hormonal levels.Conclusion. The participation of the plasminogen activation system in the pathogenesis of tumor lesions of the uterine body has been shown. The system’s “response” to the development of tumors in the uterus has both general characteristics and features that depend on the nature of the tumors and on the age-specific hormonal regulation of the body, which are most pronounced in postmenopausal women. The results obtained can be used in research aimed at clarifying the targets of targeted therapy for LM and UCEC in accordance with the age of patients.